Hubungan Parasosial di Media Sosial: Studi Pada Fandom Army di Twitter - Afitia Sagita; Donie Kadewandana (CoverAge: Journal of Strategic Communication, 2017)
Social media uploads from idols to the fans continously can create a sense of affinity for the fans. The social media uploads contain the idol's daily activities. The way the idol communicate their social media use language that similar to interpersonal communication. This enhances the parasocial relationship with fans. This study aims to find out how emotional involvement is intertwined in the parasocial relationship run by the Army Fandom. This study is using interpretative paradigm with qualitative research design. The type of research used in this study is descriptive research. The results of this study shows fans whom are Army fandom constantly interact with his idol through social media, especially Twitter. Fans also have a high self-disclosure as an Army and a high level of discernment to their idol. Fans have a high interdependence to keep in touch with things that related to their idol. Fans also have a high emotional attachment to their idols.